Role of Autologous Platelet Rich Plasma in Timely Healing of Chronic Diabetic Foot Ulcer - Marram, Muhammad Faaiz Ul; Khan, Waseem Ahmad; Imran, Muhammad; Umer, Waleed; Deen, Zahoor Muhi Ud; Malik, Fahad Nazir (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the efficacy of platelet-rich plasma in treating chronic non-healing diabetic foot ulcers, in comparison to conventional dressings. Study Design: Quasi-experimental study. Place and Duration of Study: General Surgery Department of Combined Military Hospital Rawalpindi, Pakistan from Jun- Dec 2023. Methodology: A comparative study was conducted on patients with persistent non-healing diabetic foot ulcers. The study participants were split up into two groups. In Group-A, platelet-rich plasma was injected into the ulcer’s base and the wound’s borders. In Group-B, the ulcer was treated with saline-soaked moist dressings. Every patient underwent two months of follow-up, with planned follow-up visits on 7th, 14th, 30th, 45th, and 60th days. Autologous PRP’s effectiveness in treating chronic diabetic foot ulcers was compared with conventional dressings. Results: Mean age of 120 patients was 55.98±9.71 years. 108(90%) were males and 12(10%) were females. At the end of two months, 53(88.8%) patients from Group-A showed a significant reduction in wound grade as compared to 28(46%) patients from Group-B (p=<0.001). Furthermore, 48(80%) patients from Group-A experienced complete wound healing after 02 months as compared to 14(23.3%%) patients from Group-B (p=<0.001) Conclusion: Treating chronic non-healing diabetic foot ulcers with Autologous Platelet-Rich Plasma is associated with better and expedited wound healing.